2011
DOI: 10.1080/00224499.2011.558645
|View full text |Cite
|
Sign up to set email alerts
|

HIV in Young Men Who Have Sex with Men: A Review of Epidemiology, Risk and Protective Factors, and Interventions

Abstract: Epidemiological studies have found that young men who have sex with men (YMSM) represent the majority of young people infected with HIV annually in the U.S. Further, they are one of the few risk groups to show an increase in the rate of infections in recent years. In addition to these disparities in prevalence and infection rates, there is an inequity in prevention and intervention research on this population. The purpose of this article is to review the existing YMSM literature on HIV epidemiology, correlates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
330
1
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 319 publications
(353 citation statements)
references
References 319 publications
(354 reference statements)
16
330
1
6
Order By: Relevance
“…Individuals' engagement in risky sexual behaviours or UAI has been incriminated as the main contributor to the spread of the epidemic among them (Mumtaz, Hilmi, McFarland, Kaplan, & Akala, 2011;Mustanski, Newcomb, Du-Bois, Garcia, & Grov, 2011). Consistent with the results of several previous studies (El-Sayed, IA, & El-Gueniedy, 2008;Mimiaga et al, 2009;Morineau, et al, 2011;Poon, et al, 2013), the current study confirms that having multiple casual sex partners was one of the behavioural determinants strongly associated with HIV-risk sexual practice among the participants.…”
Section: Discussionsupporting
confidence: 90%
“…Individuals' engagement in risky sexual behaviours or UAI has been incriminated as the main contributor to the spread of the epidemic among them (Mumtaz, Hilmi, McFarland, Kaplan, & Akala, 2011;Mustanski, Newcomb, Du-Bois, Garcia, & Grov, 2011). Consistent with the results of several previous studies (El-Sayed, IA, & El-Gueniedy, 2008;Mimiaga et al, 2009;Morineau, et al, 2011;Poon, et al, 2013), the current study confirms that having multiple casual sex partners was one of the behavioural determinants strongly associated with HIV-risk sexual practice among the participants.…”
Section: Discussionsupporting
confidence: 90%
“…economic insecurity, low educational attainment) have been identified in other studies with MSM who sell sex globally [21,36]. Thus, as suggested by Newman and colleagues in studies of MSM who sell sex in other low- and middle-income countries [25], interventions predicated on individual level factors, such as HIV knowledge, condom negotiation and safer sex self-efficacy, would likely be more effective if paired with interventions to increase condom access and address economic security among MSM who sell sex.
Figure 1.Conceptual model of social ecological factors associated with selling sex among men who have sex with men in Jamaica (n = 556).
…”
Section: Discussionmentioning
confidence: 88%
“…This difference may reflect the economic insecurity characteristic of the present sample, pervasive forced sex, and the lesser networking with HIV prevention outreach than among other more formal groups of MSM who sell sex [13,14]. In their review of HIV risk factors for young MSM, Mustanski and colleagues [25] suggested several potential mechanisms by which safer sex self-efficacy may be constrained in the context of selling sex, including: lacking essential skills to discuss condom use and HIV/STI with clients; condoms may not be readily available for free and, given other needs (food, shelter, clothing), may not be prioritized for purchase; MSM who are street-based sex workers may not carry condoms due to sex work criminalization and fear of being detained; and the economic insecurity that is often paired with sex work for MSM, which may lead some MSM to accede to clients who may request condomless sex for higher pay. Associations between inconsistent condom use and some of these factors (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, if Twink-identified men are more likely to participate in the gay scene, such as visiting gay bars and clubs, this may involve exposure to drugs and sex partying (Lea et al, 2013;Mustanski, Newcomb, Du Bois, Garcia, & Grov, 2011), which might explain why some higher-risk behaviors were more common in this group. In addition, for some men, engaging in receptive anal intercourse may be an expression of submissiveness.…”
Section: Discussionmentioning
confidence: 99%